A simplified approach for thermal elastohydrodynamic lubrication analysis of circular contacts using realistic lubricant properties. (December 2018) - Katyal, Puneet; Kumar, Punit
Thermal effect in elastohydrodynamic lubrication has been the subject of extensive research for several decades. The focus of this study was primarily on the development of an efficient numerical scheme to deal with the computational challenges involved in the solution of thermal elastohydrodynamic lubrication model; however, some important aspects related to the accurate description of lubricant properties such as viscosity, rheology, and thermal conductivity in elastohydrodynamic lubrication point contact analysis remain largely neglected. A few studies available in this regard are based upon highly complex mathematical models difficult to formulate and execute. The end-users may not have the specialized skill, knowledge, and time required for the development of computational codes pertaining to these models. Therefore, this paper offers a very simple approach to determine the distribution of mean fluid temperature within an elastohydrodynamic lubrication film. While it is an approximate method, it yields reasonably accurate results with only a little increase in computation time with respect to the isothermal case. Moreover, it can be added as a small module to any existing isothermal algorithm. Using this simplified thermal elastohydrodynamic lubrication model for point contacts, this work sheds some light on the importance of accurate characterization of the lubricant properties and demonstrates that the computed thermal elastohydrodynamic lubrication characteristics are highly sensitive to lubricant properties. It also emphasizes the use of appropriate mathematical models with experimentally determined parameters to account for the correct lubricant behavior.